Capacitive and diffusive contribution in strontium phosphide-polyaniline based supercapattery. (June 2020) - Iqbal, Muhammad Zahir; Faisal, Mian Muhammad; Sulman, Muhammad; Ali, Syeda Ramsha; Afzal, Amir Muhammad; Kamran, Muhammad Arshad; Alharbi, Thamer
Highlights: Strontium phosphide/PANI for asymmetric devices. Analysis of Faradaic and non-Faradaic contribution supercapattery. High specific energy as well as high specific power. Diffusive contribution is dominant at lower scan rates. Capacitive contribution is dominant at higher scan rates. Abstract: The statistics of capacitive and diffusive contribution in the supercapattery performance is analyzed via numerical approach. In this regard's strontium phosphide has been synthesized through sonochemical technique whereas PANI is obtained through polymerization. The optimized composite of strontium phosphide and PANI is designated for supercapattery device by coupling it with activated carbon. Structural, morphological, crystallinity, and elemental analysis is carried out through SEM, XRD and EDX. The electrochemical performance in three as well as two electrode assembly is investigated through CV, GCD and EIS. Supercapattery expresses excellent performance by showing 122.4 C/g specific capacity, 28.9 W h/kg energy density and 1020 W/kg power density. This device also delivered outstanding power density of 5100 W/kg in parallel with 10.95 W h/kg energy density. Later, the capacitive/diffusive contribution in the supercapattery is analyzed through a systematic approach. A total of 87.95% diffusive contribution is recorded at the scan rate of 3 mV/s which reaches up to 57.90% at 100 mV/s. On other side capacitive contribution in the device is 12.04% at lower scan rate that raises up to 42.09% at 100 mV/s. The decrease in the diffusive part and increase in the capacitive part is due to the ion's interaction time offered with electrode material at lower and higher scan rates.